A surgical challange for primary hyperparathyroidism: Intravagal parathyroid adenoma - Adem Binnetoglu; Adem Binnetoglu; Yavuz Gundogdu; Tekin Baglam; Murat Sari (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
A missed parathroid adenomas are the most common cause of surgical failure in persistent primary hyperparathyroidic patients. Abnormalities in the normal migration of the parathyroid glands during embryological development of the head and neck may result in considerable variability in the location of parathyroid tissue. Imaging studies were crucial in localizing the neoplasms in these patients. It is important to develop a strategy to systematically locate these glands either by preoperative investigations or surgical exploration. We describe a patient with persistent primary hyperparathyroidism who underwent three unsuccessful surgical procedures due to an intravagal parathyroid adenoma.